Application of Polyfolates in the Development of Electrochemical Glucose Biosensors. Issue 10 (9th September 2014) - Venckus, Tautvydas; Celiešiūtė, Raimonda; Radzevič, Aneta; Rakickas, Tomas; Vaitekonis, Šarūnas; Ruželė, Živilė; Pauliukaite, Rasa
Abstract Folic acid was polymerised electrochemically at a glassy carbon electrode surface from 0.1 mol L−1 phosphate buffer saline solution, pH 5.0, containing 0.1 mmol L−1 monomer. The obtained thin film was porous with a pore size of 50–60 nm. Since its electrochemical stability was rather short, the polyfolate film was covered with a graphene‐chitosan composite layer which increased its stability significantly. The best strategy to immobilise the enzyme was crosslinking with glutaraldehyde. The lifetime of this glucose biosensor in use was at least 12 days, on‐shelf life time was at least 30 days. The linear range was up to 1 mmol L−1 and the LOD was 0.6 µmol L−1. The first polyfolate‐based biosensor was applied to analysis of natural samples.